THE HISTORY OF THE KING'S JURISDICTION AND THE RIGHT OF THE KING'S AUTHORITY IN JUDGING (An Interpretation of the Origins of Civil and Criminal Cases) - Karimuddin Karimuddin (STIS Nahdlatul Ulama Aceh, 2020)
Judiciary in the Airlangga era was held by the king himself, and corporal punishment was only imposed by the king and on robbers and thieves. However, it also becomes a reality, justice in ancient times was also carried out by certain officials. In fact, in royal territorial law units, the head of the unit also carries out the judiciary based on customary law. Some of the results of research by Dutch experts on the existence of a separation of the judiciary during the kingdom era in Indonesia, such as the pradata court and the unified court. Pradata cases were tried or decided by the king himself while unified cases were tried by royal officials. Therefore, the author wants to examine why the king's court is different from the court of certain officials within the kingdom. So based on the results of this study, the Pradata case is a case that endangers the crown, security, and order of the kingdom, for example creating riots in the kingdom, committing murder, persecution, robbery, and others. Whereas Padu cases are cases concerning individual people's interests, for example, disputes between communities that cannot be reconciled amicably, then cases like these are tried by royal officials. The reason for distinguishing the king's court from the official court is because the cases handled by the king's court are urgent and threaten the stability and integrity of the kingdom so that the handling must be strictly enforced by the king himself. While the judiciary officials handle cases of community disputes and these cases do not threaten the existence of the kingdom, so the handling is less urgent so they are left to the officials.